(untitled) - Redaktion Sozialpsychiatrische Informationen (Sozialpsychiatrische Informationen, 2023)
Since 1970, Sozialpsychiatrische Informationen has been an interdisciplinary platform for reform-oriented psychiatry. Reports, research, and discussions in clinical as well as nonclinical areas, complement by book reviews and event information make Sozialpsychiatrische Informationen the most distributed, highest-circulation journal of its kind.The mix of single-topic special issues and issues with articles on different current topics ensures its scientific relevance and topicality.